Attentional reorientation along the meridians of the visual field: Are there different neural mechanisms at play?. Issue 13 (11th June 2020) - Steinkamp, Simon R.; Vossel, Simone; Fink, Gereon R.; Weidner, Ralph
Abstract: Hemispatial neglect, after unilateral lesions to parietal brain areas, is characterized by an inability to respond to unexpected stimuli in contralesional space. As the visual field's horizontal meridian is most severely affected, the brain networks controlling visuospatial processes might be tuned explicitly to this axis. We investigated such a potential directional tuning in the dorsal and ventral frontoparietal attention networks, with a particular focus on attentional reorientation. We used an orientation‐discrimination task where a spatial precue indicated the target position with 80% validity. Healthy participants ( n = 29) performed this task in two runs and were required to (re‐)orient attention either only along the horizontal or the vertical meridian, while fMRI and behavioral measures were recorded. By using a general linear model for behavioral and fMRI data, dynamic causal modeling for effective connectivity, and other predictive approaches, we found strong statistical evidence for a reorientation effect for horizontal and vertical runs. However, neither neural nor behavioral measures differed between vertical and horizontal reorienting. Moreover, models from one run successfully predicted the cueing condition in the respective other run. Our results suggest that activations in the dorsal and ventral attention networks represent higher‐order cognitive processes related to spatial attentional (re‐)orientating that are independent of directional tuning and that unilateral attention deficits after brain damage are based on disrupted interactions between higher‐level attention networks and sensory areas. Abstract : Due to lesion models of hemispatial neglect, many spatial cueing tasks use horizontal stimulus layouts. The vertical axis is often ignored which might bias our understanding of (re‐)orientation of spatial attention. In this study we find that attentional (re‐)orientation along both axes rely on very similar processes.